The Visual Text: Bibliographic Codes as Pragmatic Markers on a Manuscript Page - Rogos-Hebda, Justyna (Studia Anglica Posnaniensia, 2016)
This paper explores the dynamics of the textual-visual interface of a medieval manuscript page within the frameworks of historical pragmatics and pragmaphilological approaches to the study of historical texts. Whilst the former focuses on the contexts in which historical utterances, manifested as texts, occur (Jacobs and Jucker 1995: 11), the latter involves a context-based perspective in the study of individual historical texts (Jucker 2000: 91). Combining the two approaches allows for a more comprehensive study of the “visual text” (cf. Machan 2011) than has been possible for paleographic, codicological, or linguistic analyses of medieval manuscripts. The present paper adopts the “pragmatics-on-the-page” approach (cf. Carroll et al. 2013, Peikola et al. 2014) in its analysis of bibliographic codes in British Library Royal MS 18 D II, which contains the texts of Lydgate’s Troy Book and Siege of Thebes. Such visual elements of the manuscript page as mise en page, ink colour, as well as type and size of script will be examined as pragmatic markers, functioning on three levels of meaning: textual, interactional, and metalinguistic (cf. Erman 2001, Carroll et al. 2013), and providing (visual) contexts for interpreting the linguistic message of the text.